Inhaled Methane limits the mitochondrial electron transport chain dysfunction during experimental liver ischemia-reperfusion injury - Strifler Gerda (PLOS ONE, 2016)
Background: Methanogenesis can indicate the fermentation activity of the gastrointestinal anaerobic flora. Methane also has a demonstrated anti-inflammatory potential. We hypothesized that enriched methane inhalation can influence the respiratory activity of the liver mitochondria after an ischemia-reperfusion (IR) challenge. Methods: The activity of oxidative phosphorylation system complexes was determined after in vitro methane treatment of intact liver mitochondria. Anesthetized Sprague-Dawley rats subjected to standardized 60-min warm hepatic ischemia inhaled normoxic air (n = 6) or normoxic air containing 2.2% methane, from 50 min of ischemia and throughout the 60-min reperfusion period (n = 6). Measurement data were compared with those on sham-operated animals (n = 6 each). Liver biopsy samples were subjected to high-resolution respirometry; whole-blood superoxide and hydrogen peroxide production was measured; hepatocyte apoptosis was detected with TUNEL staining and in vivo fluorescence laser scanning microscopy. Results: Significantly decreased complex II-linked basal respiration was found in the normoxic IR group at 55 min of ischemia and a lower respiratory capacity (∼60%) and after 5 min of reperfusion. Methane inhalation preserved the maximal respiratory capacity at 55 min of ischemia and significantly improved the basal respiration during the first 30 min of reperfusion. The IR-induced cytochrome c activity, reactive oxygen species (ROS) production and hepatocyte apoptosis were also significantly reduced. Conclusions: The normoxic IR injury was accompanied by significant functional damage of the inner mitochondrial membrane, increased cytochrome c activity, enhanced ROS production and apoptosis. An elevated methane intake confers significant protection against mitochondrial dysfunction and reduces the oxidative damage of the hepatocytes. © 2016 Strifler et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.